THE DETERMINATION OF SPIRITUAL INTELLIGENCE, INTELLECTUAL INTELLIGENCE, PSYCHOMOTOR INTELLIGENCE ON NOBLE MORALS THROUGH THE COMPETENCE OF LECTURERS AT THE UNIVERSITY OF BATAM IN THE DIGITALIZATION ERA IN THE RIAU ISLANDS - Elli Widia, Chablullah Wibisono, Mohamad Gita Indrawan, Raymond (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As a higher education institution with the realities of life, Batam University must position itself as a reliable supplier of human resources, significantly when the Covid-19 pandemic era increased in the digital era in the business and industrial world. The research object was conducted at the University of Batam, with 240 lecturers as respondents. Data analysis was performed using the Structural Equation Model (SEM) method. The software used for structural analysis is AMOS* version 24. The results of the discussion are obtained as follows: The Determination of the Intellectual Intelligence variable on the Competence variable is positive and not significant, the Determination of the Spiritual Intelligence variable on the Competence variable is significantly positive, the Psychomotor Intelligence variable determination on the Competence variable is significantly positive, the Intellectual Intelligence variable Determination on the Noble Morals variable is positively significant, the Spiritual Intelligence variable Determination The Determination of the Noble Morals variable is significantly positive, the Psychomotor Intelligence variable Determination on the Noble Morals variable is positive and insignificant, the Competence variable determination against the Noble Morals variable is significantly positive, Multiple Square Correlation for Competence = 0892, for Noble Morals = 0.996. This research proved that there were problems during the Covid 19 Pandemic Era and the Digital Era, namely the Intellectual Intelligence variable on the Competence variable and the Psychomotor Intelligence variable on the Noble Morals variable.